Kontraktor Pertambangan: Sebuah Tinjauan Hak-hak Normatif Pekerja - Buwana, Sudibyo Aji Narendra; Fardiansyah, Hardi; Rizkia, Nanda Dwi (Widya Yuridika, 2024)
Normative provisions based on Chapter IV, Part Two of Employment, Article 25 Paragraph 3 of Law No. 6 of 2023 Concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 Concerning Job Creation to become a Law that stipulates that annual leave is given at least 12 (twelve) working days after workers or laborers have worked for 12 (twelve) months continuously. The gap in das sein is that the provisions of Chapter IV, Part Two, of Employment Article 25, Paragraph 3, of Law No. 6th, 2023, apply to workers in the company. Researchers observe that there is a gap between das sein and dass sollen. The formulation of the problem is: what are the normative rights of workers, and what are the sanctions for companies that do not provide workers' normative rights. The type of research used by researchers in this study is empirical-juridical. The research approach used is empirical-juridical, which is closely related to the case approach. The source of legal material uses primary data, namely interviews and observations conducted by researchers by visiting the research site directly. Secondary data uses primary legal materials, namely applicable laws and regulations, secondary legal materials, namely books, journals, and relevant previous research results, as well as tertiary legal materials in the form of websites. Data collection techniques using in-depth interviews and observation All primary and secondary data in this study were collected and analyzed qualitatively. Conclusions are drawn deductively. The result of his research is that the normative right to annual leave has not been implemented by the company. The conclusion is that the normative rights received by workers who are bound by PKWT at a Mining Contractor Services Company consist of economic rights, political rights, medical rights, and social rights. Sanctions for companies can be punishable by imprisonment for a minimum of 1 (one) month and a maximum of 12 (twelve) months and/or a fine of a minimum of Rp. 10,000,000.00 (ten million rupiah) and a maximum of Rp. 100,000,000.00 (one hundred million rupiah) in accordance with Chapter IV, Part Two of Employment, Article 68, Paragraph 1, of Law No. 6th, 2023, concerning Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation to become Law.